Neutralizing antibody response against the B.1.617.2 (delta) and the B.1.1.529 (omicron) variants after a third mRNA SARS‐CoV‐2 vaccine dose in kidney transplant recipients. Issue 7 (18th April 2022) - Benning, Louise; Morath, Christian; Bartenschlager, Marie; Kim, Heeyoung; Reineke, Marvin; Beimler, Jörg; Buylaert, Mirabel; Nusshag, Christian; Kälble, Florian; Reichel, Paula; Töllner, Maximilian; Schaier, Matthias; et al.
Abstract : Seroconversion after COVID‐19 vaccination is impaired in kidney transplant recipients. Emerging variants of concern such as the B.1.617.2 (delta) and the B.1.1.529 (omicron) variants pose an increasing threat to these patients. In this observational cohort study, we measured anti‐S1 IgG, surrogate neutralizing, and anti‐receptor‐binding domain antibodies three weeks after a third mRNA vaccine dose in 49 kidney transplant recipients and compared results to 25 age‐matched healthy controls. In addition, vaccine‐induced neutralization of SARS‐CoV‐2 wild‐type, the B.1.617.2 (delta), and the B.1.1.529 (omicron) variants was assessed using a live‐virus assay. After a third vaccine dose, anti‐S1 IgG, surrogate neutralizing, and anti‐receptor‐binding domain antibodies were significantly lower in kidney transplant recipients compared to healthy controls. Only 29/49 (59%) sera of kidney transplant recipients contained neutralizing antibodies against the SARS‐CoV‐2 wild‐type or the B.1.617.2 (delta) variant and neutralization titers were significantly reduced compared to healthy controls ( p < 0.001). Vaccine‐induced cross‐neutralization of the B.1.1.529 (omicron) variants was detectable in 15/35 (43%) kidney transplant recipients with seropositivity for anti‐S1 IgG, surrogate neutralizing, and/or anti‐RBD antibodies. Neutralization of the B.1.1.529 (omicron) variants was significantly reduced compared to neutralization of SARS‐CoV‐2 wild‐type or the B.1.617.2 (delta) variant for both, kidney transplant recipients and healthy controls ( p < .001 for all). Abstract : A third mRNA vaccine dose increases immunogenicity in most kidney transplant recipients but, in comparison to healthy controls, kidney recipients have significantly reduced cross‐neutralizing antibody activity against the immune‐escaping B.1.1.529 (omicron) variant.